Association of TCF7L2 Gene with Familial Combined Hyperlipidemia in Diabetes Mellitus Type 2 Females Iraqi Patients - Najwa Sh Ahmed (Journal of Global Pharma Technology, 2016)
Genomic polymorphisms of transcription factor7 like 2 TCF7L2 gene are scanned to be powerfully related to diabetes mellitus type 2 (DM2) in female Iraqi population. The point of this examination was to break down the relationship of TCF7L2 gene polymorphisms with DM2 in a very female populace of Iraq. Familial combined hyperlipidaemia (FCHL) is described by hypercholesterolaemia, hypertriacylglycerolaemia, or both. Also, instabilities in glucose metabolism are normally realized in FCHL. Thus, we guessed that TCF7L2 may add to the genetic defenselessness for this basic dyslipidaemia.. Techniques: 70 DM2 female patients and 60 healthy samples were chosen for the current study. Has been conducted designedly of one primer for amplification to scan the gene and using PCR technique with sequencing. We examined the impact of the TCF7L2 variations on FCHL and its segment characteristics triacylglycerol (TG), apolipoprotein B (ApoB) and total cholesterol (TC). The Results: For total participants, the (T/C vs. TG + GT) were significantly greater in samples with DM2 than in healthy controls, and FCHL, TC, ApoB or glucose for DM2 were associated with T>C and G>T .This result revealed that the risk of DM2 was raised by the existence of the T>C and G>T genotype of TCF7L2 gene in Iraqi female. The frequency of the T allele in TCF7L2 gene was greater in DM2 patients than in healthy samples. Conclusions: Our analysis proposed that the genetic polymorphisms of TCF7L2 were significantly related with high T>C and G>T in FCHL families with DM2 in the female populace of Iraq.Keyword: DM2 ;TCF7L2; FCHL; Hypertriacylglycerolaemia.